STUDI XRD MANGAN OKSIDA BIRNESSITE YANG DIPREPARASI MELALUI METODE SOL-GEL DAN KERAMIK - Dian Anggraini; Amir Awaluddin; Pepi Helza Yanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Birnessite is a naturally occurring layered manganese oxide found as a manganese nodules in sea floor or soil deposit. In this study, birnessite was synthesized using two types of methods, solid state ceramic approach and sol-gel reaction both KMnO4 and maltose were used as reactants in these two methods. The products were then characterized using XRD for determination of phases, crystallinity and purity. The results showed the both techniques lead to the formation of birnessite with different crystallinity and purity. The ceramic method produced more crystalline and pure birnessite than that of sol-gel. The typical reaction parameters for the synthesis birnessite by the ceramic method were 3:1 mole ratio (KMnO4over maltose) calcination at 700o C for 7 hours with the 93,7% purity of birnessite. However, by the sol-gel method birnessite produced only 31,8% with the following condition 4:1 mole ratio (KMnO4 over maltose) and calcination temperature of 450o C for 2 hours.